Role of PPARs in Progression of Anxiety: Literature Analysis and Signaling Pathways Reconstruction - Olga I. Rudko; Artemii V. Tretiakov; Elena A. Naumova; Eugene A. Klimov (PPAR Research)
Peroxisome proliferator-activated receptor (PPAR) group includes three isoforms encoded by PPARG, PPARA, and PPARD genes. High concentrations of PPARs are found in parts of the brain linked to anxiety development, including hippocampus and amygdala. Among three PPAR isoforms, PPARG demonstrates the highest expression in CNS, where it can be found in neurons, astrocytes, and glial cells. Herein, the highest PPARG expression occurs in amygdala. However, little is known considering possible connections between PPARs and anxiety behavior. We reviewed possible connections between PPARs and anxiety. We used the Pathway Studio software (Elsevier). Signal pathways were created according to previously developed algorithms. SNEA was performed in Pathway Studio. Current study revealed 14 PPAR-regulated proteins linked to anxiety. Possible mechanism of PPAR involvement in neuroinflammation protection is proposed. Signal pathway reconstruction and reviewing aimed to reveal possible connection between PPARG and CCK-ergic system was conducted. Said analysis revealed that PPARG-dependent regulation of MME and ACE peptidase expression may affect levels of nonhydrolysed, i.e., active CCK-4. Impairments in PPARG regulation and following MME and ACE peptidase expression impairments in amygdala may be the possible mechanism leading to pathological anxiety development, with brain CCK-4 accumulation being a key link. Literature data analysis and signal pathway reconstruction and reviewing revealed two possible mechanisms of peroxisome proliferator-activated receptors involvement in pathological anxiety: (1) cytokine expression and neuroinflammation mechanism and (2) regulation of peptidases targeted to anxiety-associated neuropeptides, primarily CCK-4, mechanism.